Comprehend of Patho-physiological Changes & Consequential Prognosis in Marmabhighata (Injury to Marma) - Banjare, Hiarman; Meher, Susil; Baghel, Sachin kumar; Dalai, Sujit (International Journal of Scientific Research in Biological Sciences, 2019)
‘Marma’ literary communicates the sense of vital parts of the body. The science of Marma is an unique approach of Ayurveda and established to help the practice of surgery. There are total 107 Marma’s in the human body. These are classified into five types according to location, structures involved, effect and consequences or prognosis of the trauma over there. Any type of Marmabhighata (injury to Marma) is likely to produce subjective manifestations governed by the extent and the nature of injuries to the Marmas. Tridosha in the body have their Panchabhautik origin. The Pancha mahabhautas are the main constituting component of Tridosha such that, the consequence of traumatised Marma has got direct bearing on the predominance of Tridoshas over there. Any trauma to these Marmas is likely to provoke both the Shareerik and Manasik dosha which thereby affects the body (Sharira) and Mind (Mana). So, as the base (body and Mind) gets affected, the Jeevatma or Bhootatma itself ceases to exit. This changes in Marma after injury such as deformities and delayed healing mainly depends upon the consequences that occur due to patho-physiological changes over Marma.